PLATFORM MECHANICS OF HATE AND MARGINALITY: PERSPECTIVES FROM THE GLOBAL SOUTH - Eapen, Gayas; Khan, Sarah; Njathi, Wangari; Nzau , Teresia; Wambui, Rebeccah; Sekharan, Abhishek (AoIR Selected Papers of Internet Research, 2026)
This panel critically examines platform imperialism by exploring platform affordances, constraints, and the social practices they reshape. Through four case studies from India and Kenya, we challenge dominant Western theoretical frameworks, emphasizing how platforms intersect with shared histories of colonialism, racialized dispossession, and extraction across the majority world. Through this panel, we aim to generate theoretical alternatives that resonate globally while centering perspectives from the South.Platforms have become infrastructural to cultural and social reproduction, shaping institutional processes, valuation, and circulation of cultural artifacts. While existing scholarship has examined platform power through lenses of imperialism, racial capitalism, and colonialism, macro-theorizations often obscure the nuanced ways in which platform logics manifest in distinct socio-historical contexts.We introduce the concept of "platform mechanics" to analyze the encoded and institutionalized boundaries within which extraction and resistance unfold. Drawing from critical game studies, we consider platform affordances—such as encryption, content moderation, algorithmic governance, and surveillance—as sites of constraint and possibility. Our papers explore the mediation of marginality, digital repression, ethnonationalism, Islamophobia, caste segregation, and gendered power. By foregrounding platform mechanics as a framework for understanding social inequality and resistance, we invite discussions on counter-imaginaries that envision alternative platform ecosystems.